"Acciones antropogénicas en el humedal cochahuma y su incidencia en la cantidad y calidad del agua, propuesta de manejo participativo para su recuperación y mantenimiento" - Romero Argudo, Carlos Marcelo (2012)
Cochahuma wetland is an important swamp surrounded by a chain of hills and located at 2 northeastern parishes of the canton and province of Cañar, such as Honorato Vazquez and Ingapirca, its waters are deposited in rivers Molobog and Cañar, which form part of the Pacific Basin. The biophysical characteristics of the Cochahuma wetland identify it as an ecosystem of marshy and lake, it has water outcrops and remains constantly waterlogged. For many years the Ministry of Environment and other institutions related to the subject, have detected the threat of degradation and disappearance of wetlands as a result of drainage actions taken by the settlers settled in areas adjacent to the wetland area. The research meets the objectives and hypotheses raised, so that has a database of wetland watershed Cochahuma, its location, legal status and limits accessibility, biophysical, socio-economics, the relationship of the wetland community, the state of its water sources, flow and current land use. The use of satellite images and field trips allowed a comparison of the reduction in wetland area from 1985 to 2009 of 128 ha, the water analysis established the degree of eutrophication and wetland water quality and flow of major waterways.